Parameter Estimation in HIV/AIDS Epidemiological Models. - Barrios Ginart, Jorge (2010)
The validation process of mathematical models that describe practical applications usually implies the estimation of the unknown parameters that are involved. In this work, in order to estimates these parameters in the HIV/AIDS models of [7], the problem of estimating the parameters in first order ordinary differential equations with known start point is formulated and a strategy of solution is presented. It is verified as well, which is the model of HIV/AIDS that represents best the real data according with the strategy of solution.